A fully integrated nucleic acid analysis system for multiplex detection of genetic polymorphisms related to folic acid metabolism. Issue 7 (21st February 2023) - Lin, Baobao; Geng, Zhi; Chen, Yanjing; Zeng, Wu; Li, Bao; Zhang, Yan; Liu, Peng
Abstract : A fully integrated microfluidic system to automatically detect blood samples and determine the genetic polymorphisms associated with folic acid metabolism in a "sample in-answer out" style. Abstract : A sufficient intake of folic acid is essential during pregnancy, but several genetic polymorphisms reduce its absorption, threaten the lives of pregnant women and cause congenital disabilities in newborns. Traditional laboratory detection of genetic variants related to folic acid metabolism is time-consuming and labor-intensive. Microfluidics-based molecular diagnosis integrates sample pre-processing and nucleic acid amplification on-chip to achieve rapid, sensitive, high-throughput, and automated detection. Here, we developed a fully integrated microfluidic system for the detection of genetic polymorphisms related to folic acid metabolism in a "sample in-answer out" style. The system consists of nucleic acid extraction and amplification modules. During nucleic acid extraction, blood cells are lysed, and DNA is captured and eluted through a silica-gel membrane. After that, multiple gene loci are detected using loop-mediated isothermal amplification (LAMP) and the color of the reaction chamber indicates whether genetic mutations are present. The experimental results demonstrate that the system can accurately detect gene polymorphisms associated with folic acid metabolism in blood samples with high sensitivity and no cross-contamination between chambers. The blood samples of five patients were tested for mutant alleles on this system, and the test results were consistent with qPCR and DNA sequencing observations. The operation is fully automated, and the detection is completed in approximately 70 minutes. The proposed system has great potential in prenatal diagnosis and other types of nucleic acid detection.